Colorado water, January-March 1986 - Miller, Shirley, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1986)
Newsletter of the Colorado Water Resources Research Institute.
Keywords: Water resources development -- Colorado; Water-supply -- Colorado; Water use -- Colorado; Water-supply -- Management -- Colorado